2020
DOI: 10.1186/s12884-020-03314-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal syphilis treatment and pregnancy outcomes: a retrospective study in Jiangxi Province, China

Abstract: Background Studies investigating the associations of maternal syphilis treatment with birth outcomes mainly concentrated in economically developed areas. Limited data are available in economically underdeveloped areas, such as Jiangxi Province. The study aims to investigate the impact of maternal treatment on birth outcomes in Jiangxi Province, China. Methods Data were obtained from the China’s Information System of Prevention of Mother-to-Child Transmission in Jiangxi Province. All syphilis infected pregnan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
(18 reference statements)
1
22
0
Order By: Relevance
“…Another study from Brazil showed that among women attending a prenatal program, one to three PNC visits were associated with nonperformance tests for syphilis ( 29 ). Studies conducted in China showed an association between the timing of first treatment for syphilis to adverse pregnancy outcomes and CS ( 30 , 31 ), evidencing the importance of timing of the first PNC visit. In Brazil, after a positive syphilis reagent test (rapid syphilis test or VDRL), treatment can be provided during the same visit.…”
Section: Discussionmentioning
confidence: 98%
“…Another study from Brazil showed that among women attending a prenatal program, one to three PNC visits were associated with nonperformance tests for syphilis ( 29 ). Studies conducted in China showed an association between the timing of first treatment for syphilis to adverse pregnancy outcomes and CS ( 30 , 31 ), evidencing the importance of timing of the first PNC visit. In Brazil, after a positive syphilis reagent test (rapid syphilis test or VDRL), treatment can be provided during the same visit.…”
Section: Discussionmentioning
confidence: 98%
“…There was a significant relationship between birth asphyxia and women with syphilis infection. Maternal syphilis infection in pregnancy has been shown in other studies to lead to adverse birth outcomes including; spontaneous abortions, preterm birth, stillbirth and newborns who are small for gestational age [ 49 ]. Important to note is that, in Uganda, routine screening for syphilis is done at the initial antenatal visit and treatment offered to those who are infected [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, most national studies have only investigated the relationship between treatment during pregnancy and pregnancy outcome in pregnant women with syphilis infection [ 8 – 11 ], and few studies have evaluated the relationship between their treatment during pregnancy and the conversion of syphilis-specific antibodies in those children exposed to syphilis. It is worth mentioning that the change in serological titers before and after treatment was not identical in each pregnant woman with syphilis infection.…”
Section: Introductionmentioning
confidence: 99%